Ufes from open for social inclusion - Paiva Fernandes de Souza, Cláudia (Guará Journal, 2015)
This article consists of an experience report of participation and action of the coordinators and volunteers fellows UFES Extension Project Open Door, working in the Dean of Student Affairs and Citizenship. Participated in this first experience in 2014 about eight hundred students aged between 15 and 19 years from eight schools from various cities in the state of Espírito Santo, 1 north of Rio de Janeiro, accompanied by their teachers. We found that the experience in extension action served to awaken in adolescents and young people an interest in university education, hitherto far from their reality.
Keywords: Teens; Young; Social inclusion; Formation